Immediate renal transplantation after radical prostatectomy for low‐risk prostate cancer. (24th September 2012) - Kreydin, Evgeniy I.; Ko, Dicken S. C.
Abstract Introduction For most cancers, a two‐ to five‐yr period with no evidence of disease must be demonstrated before organ transplantation. The natural history of prostate cancer is unique both because of extensive pre‐treatment screening and the ease of post‐treatment monitoring for recurrence. Using available predictive models for prostate cancer recurrence, we examine whether current evidence supports a prolonged waiting period after radical prostatectomy and before renal transplantation. Materials and Methods A MedLine search was conducted to identify five series (published between 2000 and 2011), which examined biochemical recurrence (BCR) after prostatectomy for low‐risk prostate cancer. The likelihood of BCR at one, two, and five yr after radical prostatectomy was identified for each series. Results Each of the analyzed series demonstrated that the likelihood of BCR after radical prostatectomy for low‐risk prostate cancer was identical at one, two, and five yr and did not exceed 5%. Conclusions The likelihood of BCR does not increase during the first five yr after radical prostatectomy for low‐risk prostate cancer. Additionally, the risk of recurrence approaches zero during this period. Therefore, current evidence does not support the mandated waiting period of five yr before organ transplantation.